Fatal Granulomatous Meningoencephalitis associated to Mycobacterium Mucogenicum-like Microorganism: a Case Report - Sariol, Carlos A.; Galib, Yussef; Pantoja, Petraleigh; Colón, Lillian E.; González, Anarda; Tormos, Lee Marie; Santana, Jorge L.; Luciano, Carlos A.; González-Martínez, Janis; Kraiselburd, Edmundo N. (Puerto Rico Health Sciences Journal, 2009)
Mycobacterium mucogenicum is rarely associated to human infections. However, in the last year, a few reports of sepsis and fatal cases of central nervous systems have been documented. Here we report a fatal case of granulomatous meningoencephalitis of three weeks of evolution where DNA from a M. mucogenicum-like microorganism was identified post-mortem in samples of brain tissue.